2021
DOI: 10.7602/jmis.2021.24.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of recurrence following common bile duct exploration for choledocholithiasis

Abstract: Purpose: The purpose of this study was to investigate the recurrence factors of choledocholithiasis after common bile duct (CBD) exploration.Methods: From January 2000 to December 2018, we retrospectively reviewed 253 patients who underwent CBD exploration surgery. We excluded 100 cases who had residual stone, combined major surgery, or follow-up loss after surgery. Total of 153 patients were included, and we investigated the recurrence factors of choledocholithiasis. Various variables such as patients' demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This is because gallstones have a propensity to migrate into the CBD and block the flow of bile. This disrupted flow hinders the effective clearance of all stones, resulting in the presence of residual small stones within the duct and subsequently leading to CBD stone formation [18, 19]. In this study, the LCBDE group had the lowest recurrence rate of CBDS, which could be attributed to the concurrent performance of cholecystectomy.…”
Section: Discussionmentioning
confidence: 79%
“…This is because gallstones have a propensity to migrate into the CBD and block the flow of bile. This disrupted flow hinders the effective clearance of all stones, resulting in the presence of residual small stones within the duct and subsequently leading to CBD stone formation [18, 19]. In this study, the LCBDE group had the lowest recurrence rate of CBDS, which could be attributed to the concurrent performance of cholecystectomy.…”
Section: Discussionmentioning
confidence: 79%
“…A history of cholecystectomy, WBC count ≥11.0 × 10 9 /L, preoperative TBIL level ≥ 36.5 mmol/L, number of stones ≥2, maximum stone diameter ≥ 0.85 cm, and T-tube drainage were independent risk factors affecting CBDS recurrence in elderly patients after choledocholithotomy. A history of cholecystectomy and the placement of a T-tube drainage catheter are independent risk factors as compared to other factors and have been rarely reported as significant factors of CBDS recurrence in previous studies ( 2 , 13 , 23 ).…”
Section: Discussionmentioning
confidence: 95%
“…Improper placement of the T-tube can lead to the twisting or bending of the CBD, while prolonged T-tube drainage can increase the risk of bacterial infections within the bile duct, which may contribute to the high recurrence rate of CBDS. It is worth noting that when surgeons suspect the potential recurrence of CBDS after surgery, they often choose to place a T-tube, which may lead to selection bias ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Presentation later than that is thought to be secondary to migratory surgical clips as it acts as a nidus for stone formation. There are studies that revealed common bile duct (CBD) stones formation is associated with bile duct stricture, periampullary diverticulum, parasites or foreign bodies within bile duct or other factors that can cause bile stasis [8] . Current evidence suggests endoscopic ultrasound or magnetic resonance cholangiopancreatography as the investigation of choice for CBD stones however CT scan is important in looking for features of CBD stone, malignancy coexisting and to investigate for other causes of abdominal pain [9] .…”
Section: Case Discussionmentioning
confidence: 99%